Oropouche Virus Disease Among U.S. Travelers — United States, 2024 - Morrison, Andrea; White, Jennifer L.; Hughes, Holly R.; Guagliardo, Sarah Anne J.; Velez, Jason O.; Fitzpatrick, Kelly A.; Davis, Emily H.; Stanek, Danielle; Kopp, Edgar; Dumoulin, Peter; Locksmith, Timothy; Heberlein, Lea; et al. (MMWR. Morbidity and mortality weekly report, 2024)
Beginning in late 2023, Oropouche virus was identified as the cause of large outbreaks in Amazon regions with known endemic transmission and in new areas in South America and the Caribbean. The virus is spread to humans by infected biting midges and some mosquito species. Although infection typically causes a self-limited febrile illness, reports of two deaths in patients with Oropouche virus infection and vertical transmission associated with adverse pregnancy outcomes have raised concerns about the threat of this virus to human health. In addition to approximately 8,000 locally acquired cases in the Americas, travel-associated Oropouche virus disease cases have recently been identified in European travelers returning from Cuba and Brazil. As of August 16, 2024, a total of 21 Oropouche virus disease cases were identified among U.S. travelers returning from Cuba. Most patients initially experienced fever, myalgia, and headache, often with other symptoms including arthralgia, diarrhea, nausea or vomiting, and rash. At least three patients had recurrent symptoms after the initial illness, a common characteristic of Oropouche virus disease. Clinicians and public health jurisdictions should be aware of the occurrence of Oropouche virus disease in U.S. travelers and request testing for suspected cases. Travelers should prevent insect bites when traveling, and pregnant persons should consider deferring travel to areas experiencing outbreaks of Oropouche virus disease.